STRATEGI PENATAAN RUANG TERBUKA HIJAU YANG ADAPTIF TERHADAP BENCANA GEMPA BUMI, TSUNAMI DAN LIKUIFAKSI DI KOTA PALU (Jurnal Arsitektur ARCADE, 2026)
This study aims to formulate a strategy for developing green open space (GTH) that is adaptive to earthquakes, tsunamis, and liquefaction in Palu City. The research method is qualitative, with data collected through literature studies, document analysis, field observations, and in-depth interviews. The qualitative approach was chosen to gain a deeper understanding of the function of green open space in a social and ecological context, community perceptions of risk, and spatial planning practices. The results show that green open space has strategic potential in three main aspects: (1) risk reduction through vegetation, soil permeability, and the function of space as an evacuation zone; (2) adaptive functions in the form of transition spaces, safe gathering places, and buffers against tsunami flow directions and potential landslides; and (3) social recovery functions that strengthen community capacity in facing disasters.